2020
DOI: 10.1136/bcr-2020-234565
|View full text |Cite
|
Sign up to set email alerts
|

Seropositive anti-MOG antibody-associated acute disseminated encephalomyelitis (ADEM): a sequelae ofMycoplasmapneumoniaeinfection

Abstract: Acute disseminated encephalomyelitis (ADEM) is a demyelinating, autoimmune disease of the central nervous system (CNS). It causes motor and sensory deficits, altered mental status and other neurological symptoms. Though rarely fatal, it has been associated with residual motor and neurocognitive deficits. Our case consisted of a 4-year-old girl who presented with fatigue and unsteady gait after a respiratory illness. During her hospital course, she became progressively weaker and experienced seizures. Imaging s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It is unclear whether repetitive irritability was a symptom of ADEM, as the patient may have had intussusception-or mesenteric lymphadenopathy-associated irritability. Several cases of mycoplasma infection-associated ADEM have been reported to involve immune-mediated demyelination following respiratory in- fection; in those cases, the bacterium was detected in respiratory samples but not in CSF samples, as in our case [5][6][7][8]. Furthermore, our patient showed an excellent response to steroid pulse therapy, indicating an immune-mediated etiology of ADEM secondary to mycoplasma infection.…”
mentioning
confidence: 56%
“…It is unclear whether repetitive irritability was a symptom of ADEM, as the patient may have had intussusception-or mesenteric lymphadenopathy-associated irritability. Several cases of mycoplasma infection-associated ADEM have been reported to involve immune-mediated demyelination following respiratory in- fection; in those cases, the bacterium was detected in respiratory samples but not in CSF samples, as in our case [5][6][7][8]. Furthermore, our patient showed an excellent response to steroid pulse therapy, indicating an immune-mediated etiology of ADEM secondary to mycoplasma infection.…”
mentioning
confidence: 56%
“…M. pneumoniae infection has also been reported, but it is relatively rare [ 6 ]. The MOGAD presenting as ADEM secondary to M. pneumoniae infection has only been reported by Bonagiri P et al [ 4 ]. The case we report is unique because it represents a biphasic course.…”
Section: Discussionmentioning
confidence: 99%
“…In children, ADEM is a common clinical manifestation of MOGAD [ 2 ], and is thought to be related to previous stimuli such as a viral infection or immunity, with an annual incidence of approximately 0.3–0.6 per 100 000 children [ 3 ]. ADEM cases caused by M. pneumoniae infection have been confirmed, but there are few reports of anti-MOG -IgG-related ADEM caused by M. pneumoniae infection [ 4 ]. However, the pathogenesis of CNS demyelination induced by M. pneumoniae infection remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…ADEM is the most common manifestation in the pediatric population and often occurs after infection with EBV, measles, influenza, enterovirus, coronavirus, herpes simplex and, rarely, Mycoplasma pneumoniae [ 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 ]. Recently, it has been observed that previous infection is more common during the monophasic course of the disease [ 191 ].…”
Section: Mogadmentioning
confidence: 99%